(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In the context of globalization and international communication, language learning ability has become a core professional competence for future teachers. Pre-service teachers are expected not only to master foreign languages but also to develop the pedagogical capacity to facilitate language acquisition in learners. This article examines the pedagogical aspects of developing language learning ability in pre-service teachers. Using a mixed-methods approach, the study analyzes theoretical foundations, instructional strategies, and empirical data collected from teacher training institutions. The results demonstrate that learner-centered pedagogy, metacognitive strategy training, and reflective practice significantly enhance language learning ability. The findings contribute to improving teacher education curricula and pedagogical practices aimed at preparing linguistically competent educators.